20.6k views
4 votes
Subtract the polynomials. (3x2+10x+5y)−(−5x2+2x−6y)

User DrBug
by
6.0k points

1 Answer

0 votes

Answer:


=8x^2+8x+11y

Explanation:


\left(3x^2+10x+5y\right)-\left(-5x^2+2x-6y\right)\\\mathrm{Remove\:parentheses}:\quad \left(a\right)=a\\=3x^2+10x+5y-\left(-5x^2+2x-6y\right)\\=3x^2+10x+5y+5x^2-2x+6y\\=3x^2+5x^2+10x-2x+5y+6y\\\mathrm{Add\:similar\:elements:}\:3x^2+5x^2=8x^2\\=8x^2+10x-2x+5y+6y\\\mathrm{Add\:similar\:elements:}\:10x-2x=8x\\=8x^2+8x+5y+6y\\\mathrm{Add\:similar\:elements:}\:5y+6y=11y\\=8x^2+8x+11y\\

User Doug Kent
by
5.3k points